Method for measuring porosity of trace compact rock crushed sample based on amphiphilic saturated liquid nuclear magnetic resonance method

Through the method based on the amphiphilic saturated liquid NMR method, the problem of difficult to measure the porosity of dense rocks is solved, and the porosity is quickly and accurately measured in the case of insufficient sample volume, which improves the prediction and development efficiency of oil and gas reservoirs.

CN119846008APending Publication Date: 2025-04-18NANJING UNIV +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510029783.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to accurately measure the porosity of dense rocks, especially in the case of insufficient sample volume.

Method used

The sample was pulverized by grinding and using octamethylcyclotetrasiloxane as the probe liquid to saturate the sample and calculate the porosity.

Benefits of technology

It realizes rapid and non-destructive determination of the porosity of dense rocks in the case of insufficient sample volume, and improves the prediction and exploration and development efficiency of dense oil and gas reservoirs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119846008A_ABST
    Figure CN119846008A_ABST
Patent Text Reader

Abstract

The invention discloses a method for measuring the porosity of a micro compact rock crushed sample based on an amphiphilic saturated liquid nuclear magnetic resonance method, and relates to the technical field of rock analysis. The porosity of the rock can be quickly, simply and effectively obtained, and the method has important practical significance for improving prediction, exploration and development of compact oil and gas reservoirs. Comprising the following steps: grinding and crushing a compact rock sample, and carrying out saturation treatment on the compact rock sample by using amphiphilic saturated liquid octamethylcyclotetrasiloxane; performing nuclear magnetic resonance testing on the saturated compact rock sample to obtain a nuclear magnetic resonance signal of the saturated compact rock sample; drying the saturated compact rock crushed sample, and carrying out nuclear magnetic resonance testing to obtain a nuclear magnetic resonance signal of the compact rock dried sample; and calculating the porosity of the compact rock sample. The method is applied to the aspect of obtaining the porosity of the compact rock, the porosity of the sample is rapidly and nondestructively determined through a nuclear magnetic resonance instrument, and the problem that the porosity of the sample cannot be measured under the condition that the sample amount is insufficient is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rock analysis, and in particular to a method for measuring the porosity of a trace dense rock crushed sample based on an amphiphilic saturated liquid nuclear magnetic resonance method. Background Art

[0002] Unconventional reservoirs contain abundant tight oil and gas resources, but their complex micro-nano pore structures pose great challenges to the prediction and production of tight rock reservoirs. Generally, the distribution and accumulation of unconventional oil and gas depend to a large extent on the pore space of tight reservoirs. In order to improve the efficiency of exploration and development of tight oil and gas, it is particularly important to accurately obtain the reservoir porosity. Tight rocks have the characteristics of poor permeability and rich in clay minerals and organic matter, making it difficult to accurately characterize the porosity of tight rocks. As a non-destructive testing technology, nuclear magnetic resonance can quickly detect the nuclear magnetic resonance signal of fluids in rock pores. The intensity of the nuclear magnetic resonance signal can reflect the number of hydrogen atoms in the detection area, but the traditional nuclear magnetic resonance test of rock porosity requires the acquisition of rock standard column samples. When the sample is insufficient, the porosity of the rock cannot be obtained by the nuclear magnetic resonance method. Summary of the invention

[0003] In view of the above problems, the present invention proposes a method for measuring the porosity of trace dense rock crushed samples based on amphiphilic saturated liquid nuclear magnetic resonance, which can quickly, simply and effectively obtain the porosity of the rock, and has important practical significance for improving the prediction and exploration and development of tight oil and gas reservoirs.

[0004] The technical solution of the present invention is: carry out according to the following steps: Step 1: Select a dense rock sample, pre-treat the sample, and grind the dense rock sample into powder using a mortar and a mortar column; then, use an amphiphilic saturated liquid octamethylcyclotetrasiloxane (OMCTS) to saturate a trace amount of dense rock; Step 2: After saturation, take out the sample and use a flexible water-absorbing material to wipe off the liquid attached to the surface of the sample, and then perform a nuclear magnetic resonance test on the sample; Step 3, drying the saturated dense rock sample, after drying, taking out the dried sample for nuclear magnetic resonance testing, the test parameters are the same as step 2; Step 4, calculating the porosity of the dense rock sample; Step 4.1, selecting standard octamethylcyclotetrasiloxane solutions of different masses, performing nuclear magnetic resonance tests under the same test parameters as in step 2 and step 3, and performing linear fitting on the nuclear magnetic resonance parameters after the tests; Step 4.2, subtract the NMR data of the saturated sample from the NMR data of the dry sample, and then substitute the difference into the linear fitting equation to obtain the mass of the octamethylcyclotetrasiloxane solution in the saturated sample; Step 4.3, converting the volume of the octamethylcyclotetrasiloxane solution in the saturated sample by the mass binding density of the octamethylcyclotetrasiloxane solution; Step 4.4, convert the mass of the dry sample into the volume of the dry sample by combining the density of the dense rock; Step 4.5: Divide the volume of the octamethylcyclotetrasiloxane solution in the saturated sample by the volume of the dry sample and multiply by 100% to obtain the porosity of the rock.

[0005] Furthermore, the preprocessing steps in step 1 are: The dense rock sample was pre-treated for oil washing by Soxhlet extraction. The dense rock sample was placed in an extraction cylinder and connected to a flask containing a mixed solvent of dichloromethane and methanol. Condensed water was introduced and the flask was immersed in a constant temperature water bath at 60-65°C for extraction for at least 72 hours until the solvent in the extraction cylinder was colorless and transparent. The mixing ratio of dichloromethane and methanol was 93:7.

[0006] Furthermore, the mesh size of the crushed sample in step 1 is 20-35 meshes; the standard mesh size of the crushed dense rock sample is obtained by sorting the sample using the USDA (US Department of Agriculture) standard sieve; Step 1: After crushing, the crushed dense rock sample is dried at 60°C for 24 hours to remove water and volatile impurities in the sample pores. The dried sample is placed in an octamethylcyclotetrasiloxane solution and evacuated using a vacuum pump for 24 hours. The vacuum degree is -0.1MPa, and the liquid enters the pores of the sample through vacuum self-absorption.

[0007] Further, the drying process of step 3 is: The saturated dense rock sample was placed in an oven and dried at 60°C for 24 hours until the weight of the sample no longer changed.

[0008] Furthermore, step 4.1 is specifically as follows: The octamethylcyclotetrasiloxane standard solution is placed in a low-field nuclear magnetic resonance experimental device, and a low-field nuclear magnetic resonance experimental test is carried out to obtain the nuclear magnetic resonance signals of solutions of different masses, and establish a linear relationship between the signal and the mass of octamethylcyclotetrasiloxane; a linear fitting equation y=24355x+427.28 is obtained, and the correlation R 2 =0.9999.

[0009] Furthermore, in steps 2, 3, and 4, the NMR parameters used the CPMG sequence, with an echo interval of 0.08 ms, a call-back sequence of 10,000, a waiting time of 10,000 ms, and a scanning number of 64 times.

[0010] The present invention is applied to obtaining the porosity of dense rocks, and the porosity of samples is determined quickly and non-destructively by a nuclear magnetic resonance instrument, thereby making up for the problem that the porosity of samples cannot be determined when the sample quantity is insufficient.

[0011] The present invention takes into account that the normal measurement of porosity under national standards requires block samples and column samples for measurement. In the case of a small number of samples and low sample quality (less than 3g after grinding, and even less than 1g after drying and screening), not only is the error in weighing large, but also the accuracy requirements for measuring instruments are very high. Therefore, it is actually impossible to determine the porosity of a sample with a small amount of sample by traditional means. Accordingly, this case tests the signal of octamethylcyclotetrasiloxane in nuclear magnetic resonance and then calculates the porosity. Its advantage is that the porosity of the sample can be tested with only a small amount of sample.

[0012] The amphiphilic probe liquid used in the present invention is octamethylcyclotetrasiloxane, which is amphiphilic and is conducive to entering both organic pores and inorganic mineral pores, and can better saturate the pores. Compared with the commonly used probe liquid water, the nuclear magnetic resonance signal of octamethylcyclotetrasiloxane is stronger and the test effect is better.

[0013] The present invention is based on nuclear magnetic resonance technology and uses nuclear magnetic resonance to quickly detect the nuclear magnetic resonance signals of amphiphilic saturated liquids in rock pores. Through the difference in nuclear magnetic signals between saturated samples and dry samples and the linear relationship between saturated liquids of different masses and nuclear magnetic signals, the porosity of the sample can be quickly and non-destructively determined using only a small amount of sample, thus making up for the problem that the porosity of the sample cannot be determined when the sample quantity is insufficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a schematic diagram of the analysis method flow of an embodiment of the present invention; Figure 2 This is an image of the linear relationship between octamethylcyclotetrasiloxane liquids of different masses and nuclear magnetic resonance signals obtained in an embodiment of the present invention. DETAILED DESCRIPTION

[0015] In order to clearly illustrate the technical features of this patent, this patent is elaborated in detail below through a specific implementation method and in combination with its accompanying drawings.

[0016] The steps include: Step 1: Select a dense rock sample, pre-treat the sample using the Soxhlet extraction method, and then grind the dense rock sample using a mortar and a bowl column to obtain a 20-35 mesh crushed sample.

[0017] In the present invention, preferably, the dense rock sample is pretreated with oil washing by Soxhlet extraction, the dense rock sample is placed in an extraction cylinder and connected to a flask filled with a mixed solvent of dichloromethane and methanol, condensed water is introduced, and the flask is immersed in a constant temperature water bath at 60-65°C for extraction for at least 72 hours, until the solvent in the extraction cylinder is colorless and transparent. Specifically, the dense rock sample is placed in an extraction cylinder and connected to a flask filled with a mixed solvent of dichloromethane and methanol (93:7), condensed water is introduced, and the flask is immersed in a constant temperature water bath at 60-65°C, so that the mixed solvent is continuously refluxed and extracted for at least 72 hours, during which the mixed solvent is replenished in time according to the evaporation situation, until the solvent in the extraction cylinder is colorless and transparent, that is, it is considered that all the oil in the pores of the dense rock is extracted cleanly.

[0018] Then, the crushed dense rock samples were dried at 60°C for 24 hours to remove water and volatile impurities in the sample pores. The dried samples were placed in octamethylcyclotetrasiloxane and evacuated using a vacuum pump for 24 hours (vacuum degree was -0.1MPa), and the liquid entered the pores of the sample through vacuum self-absorption.

[0019] Step 2: After saturation, take out the sample and use a flexible water-absorbing material to wipe off the liquid attached to the surface of the sample, and then perform a nuclear magnetic resonance test on the sample. The nuclear magnetic resonance parameters use the CPMG sequence, the echo interval is 0.08ms, the callback sequence is 10,000, the waiting time is 10,000ms, and the number of scans is 64 times.

[0020] Step 3: Place the saturated dense rock sample in an oven and dry it at 60°C for 24 hours until the weight of the sample no longer changes. After drying, take out the dried sample for nuclear magnetic resonance testing with the same test parameters as step 2.

[0021] Step 4, calculating the porosity of the dense rock sample; Step 4.1, select standard octamethylcyclotetrasiloxane solutions of different masses, perform NMR tests under the same test parameters as in Step 2 and Step 3, and perform linear fitting on the NMR parameters after the test to obtain the linear fitting equation y=24355x+427.28, with a correlation R 2 =0.9999; Step 4.2, subtract the NMR data of the saturated sample from the NMR data of the dry sample, and then substitute the difference into the linear fitting equation to obtain the mass of the octamethylcyclotetrasiloxane solution in the saturated sample; Step 4.3, converting the volume of the octamethylcyclotetrasiloxane solution in the saturated sample by the mass binding density of the octamethylcyclotetrasiloxane solution; Step 4.4, convert the mass of the dry sample into the volume of the dry sample by combining the density of the dense rock; Step 4.5: Divide the volume of the octamethylcyclotetrasiloxane solution in the saturated sample by the volume of the dry sample and multiply by 100% to obtain the porosity of the rock.

[0022] In order to more clearly and in detail introduce the method for measuring the porosity of trace dense rock crushed samples based on the amphiphilic saturated liquid nuclear magnetic resonance method provided by the embodiment of the present invention, it will be described in conjunction with specific embodiments below.

[0023] The nuclear magnetic resonance instrument used in the present invention is a NMRC12-010V nuclear magnetic resonance instrument produced by Suzhou Newmai Company.

[0024] Take the tight sandstone sample of Chang 8 reservoir in the Ordos Basin as an example: Step 1. Select 5-10 g of dense sandstone samples of sample 1, sample 2, and sample 3 respectively, perform oil washing pretreatment by Soxhlet extraction method, grind the samples with a mortar and a bowl column, and use a standard mesh to select 20-35 mesh crushed samples.

[0025] Then, the crushed dense sandstone sample was dried at 60°C for 24 hours, and the dried sample was immersed in octamethylcyclotetrasiloxane and vacuumed for 24 hours using a vacuum pump.

[0026] Step 2: After saturation, take out the sample, wipe off the liquid attached to the particle surface with a sponge, and then perform a nuclear magnetic resonance test on the sample. The nuclear magnetic resonance test parameters use a CPMG sequence, an echo interval of 0.08ms, a call-back sequence of 10,000, a waiting time of 10,000ms, and a scanning number of 64 times to obtain the saturated sample nuclear magnetic resonance signal data.

[0027] Step 3: Dry the saturated dense sandstone sample at 60°C for 24 hours, and perform a dry sample NMR test under the same test parameters to obtain the dry sample NMR signal data. The NMR test parameters use a CPMG sequence, an echo interval of 0.08ms, a call-back sequence of 10,000, a waiting time of 10,000ms, and a scanning number of 64 times to obtain the saturated sample NMR signal data.

[0028] Step 4: First, use nuclear magnetic resonance to test octamethylcyclotetrasiloxane of different masses, establish a linear fitting relationship between octamethylcyclotetrasiloxane and the nuclear magnetic resonance signal, and then calculate the porosity of the dense rock sample in combination with the test results of steps 2 and 3.

[0029] The porosity results obtained by calculation are shown in Table 1.

[0030] Table 1 Experimental data of sample 1, sample 2 and sample 3

[0031] Considering that the density of the dense rock used in step 4.4 above is a given value, the range is 2.5~2.6 g / cm 3 Therefore, in this example, the boundary values ​​of the range are used to calculate the NMR porosity. The calculation results show that the porosity is between 2.5 and 2.6 g / cm 3 When the density of dense rock is given within the range, the final NMR porosity results are similar. Therefore, the size of the specific given value has little effect on the result. In practical application, any value within the range can be given.

[0032] Comparative Example: The same dense samples 1-3 as above were tested for porosity using an AP-121-003-1 helium porosimeter, and the porosities obtained are shown in Table 2.

[0033] Table 2

[0034] As can be seen from Table 2, the porosity measured in the experimental example is basically close to that in the control example. The porosity data obtained by the experimental example test is larger, indicating that there are partially closed pores in the pores. In the present invention, the closed pores in the dense rock are connected by grinding and crushing the sample, and the measured porosity includes the closed pores. Therefore, this method can more accurately obtain the porosity in the dense rock and has good credibility.

[0035] There are many specific implementation ways of the present invention. The above is only the preferred implementation mode of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements can be made without departing from the principle of the present invention. These improvements should also be regarded as the protection scope of the present invention.

Claims

1. A method for measuring the porosity of a trace amount of dense rock crushed sample based on amphiphilic saturated liquid nuclear magnetic resonance method, characterized in that: Follow these steps: Step 1, selecting a dense rock sample, pre-treating the sample, and then grinding the dense rock sample; then, using amphiphilic saturated liquid octamethylcyclotetrasiloxane to saturate a trace amount of dense rock; Step 2: After saturation, take out the sample and use a flexible water-absorbing material to wipe off the liquid attached to the surface of the sample, and then perform a nuclear magnetic resonance test on the sample; Step 3, drying the saturated dense rock sample, after drying, taking out the dried sample for nuclear magnetic resonance testing, the test parameters are the same as step 2; Step 4, calculating the porosity of the dense rock sample; Step 4.1, selecting standard octamethylcyclotetrasiloxane solutions of different masses, performing nuclear magnetic resonance tests under the same test parameters as in step 2 and step 3, and performing linear fitting on the nuclear magnetic resonance parameters after the tests; Step 4.2, subtract the NMR data of the saturated sample from the NMR data of the dry sample, and then substitute the difference into the linear fitting equation to obtain the mass of the octamethylcyclotetrasiloxane solution in the saturated sample; Step 4.3, converting the volume of the octamethylcyclotetrasiloxane solution in the saturated sample by the mass binding density of the octamethylcyclotetrasiloxane solution; Step 4.4, convert the mass of the dry sample into the volume of the dry sample by combining the density of the dense rock; Step 4.5: Divide the volume of the octamethylcyclotetrasiloxane solution in the saturated sample by the volume of the dry sample and multiply by 100% to obtain the porosity of the rock.

2. The method for measuring the porosity of a trace amount of dense rock crushed sample based on the amphiphilic saturated liquid nuclear magnetic resonance method according to claim 1 is characterized in that: The preprocessing steps in step 1 are: The dense rock sample is subjected to oil washing pretreatment by Soxhlet extraction method. The dense rock sample is placed in an extraction cylinder and connected to a flask filled with a mixed solvent of dichloromethane and methanol. Condensed water is introduced and the flask is immersed in a constant temperature water bath at 60-65°C for extraction for at least 72 hours until the solvent in the extraction cylinder is colorless and transparent.

3. The method for measuring the porosity of a trace amount of dense rock crushed sample based on amphiphilic saturated liquid nuclear magnetic resonance method according to claim 1 is characterized in that: The mesh size of the crushed sample in step 1 is 20-35 mesh; Step 1: After crushing, the crushed dense rock sample is dried at 60°C for 24 hours to remove water and volatile impurities in the sample pores. The dried sample is placed in an octamethylcyclotetrasiloxane solution and evacuated using a vacuum pump for 24 hours. The vacuum degree is -0.1MPa, and the liquid enters the pores of the sample through vacuum self-absorption.

4. The method for measuring the porosity of a trace amount of dense rock crushed sample based on amphiphilic saturated liquid nuclear magnetic resonance method according to claim 1 is characterized in that: The drying process of step 3 is: The saturated dense rock sample was placed in an oven and dried at 60°C for 24 hours until the weight of the sample no longer changed.

5. The method for measuring the porosity of a trace amount of dense rock crushed sample based on the amphiphilic saturated liquid nuclear magnetic resonance method according to claim 1 is characterized in that: Step 4.1 is as follows: The octamethylcyclotetrasiloxane standard solution is placed in a low-field nuclear magnetic resonance experimental device, and a low-field nuclear magnetic resonance experimental test is carried out to obtain the nuclear magnetic resonance signals of solutions of different masses, and establish a linear relationship between the signal and the mass of octamethylcyclotetrasiloxane; a linear fitting equation y=24355x+427.28 is obtained, and the correlation R 2 =0.9999.

6. The method for measuring the porosity of a trace amount of dense rock crushed sample based on amphiphilic saturated liquid nuclear magnetic resonance method according to claim 1 is characterized in that: In steps 2, 3, and 4, the CPMG sequence was used as the NMR parameter, with an echo interval of 0.08 ms, a call-back sequence of 10,000, a waiting time of 10,000 ms, and 64 scans.

Citation Information

Patent Citations

  • Calibration method for representing dense sandstone pore size distribution by adopting nuclear magnetic resonance

    CN104634718A

  • Measurement method of pore size distribution characteristic of oil-bearing dense sandstone

    CN107271346A

  • Method for measuring pore size distribution characteristics of oil-containing rock in unconventional oil and gas reservoir

    CN111562206A

  • Method for evaluating thickness of water film after water-phase imbibition flowback of gas reservoir rock containing expansive clay

    CN113514382A

  • Standard sample for testing porosity of engineering rock core and measuring method

    CN116124665A